Robotic transvaginal natural orifice transluminal endoscopic surgery for bilateral salpingo oophorectomy - Lior Lowenstein; Emad Matanes; Zeev Weiner; Jan Baekelandt (Elsevier, 2020)
Objectives: The vaginal surgical approach has not become the standard of care, despite its advantages. The Hominis™ Surgical System is a humanoid shaped robot-assisted system that was designed specifically for robotic vaginal natural orifice transluminal endoscopic surgery (RvNOTES). We aimed to present our experience with the first RvNOTES bilateral salpingo-oophorectomy (BSO) performed by the Hominis system. Study design: A two-center prospective study of BSO by RvNOTES in women with nonmalignant indications conducted between August and December 2018. Women older than 18 years were offered to participate. Exclusion criteria included a history of abdominal malignancy, pelvic or abdominal irradiation, Crohn's disease, pelvic inflammatory disease, severe infections in the lower abdomen, active diverticulitis, deep infiltrating recto-vaginal endometriosis, and an active vaginal infection. The primary outcome of the study was the rate of conversion to open or laparoscopic approaches. Secondary outcomes included intra- and postoperative adverse events, operative time, estimated blood loss, length of hospital stay, and 6-week follow-up assessment. Results: Eight women aged 50-70 years with BMI of 19-30 kg/m2 were recruited. All the procedures were completed successfully without conversions to open surgery. No intraoperative complications were observed. Median blood loss was 10 mL (range: 10−50). The median duration of the procedure was 45 min (range: 38−91), and decreased over the study period. Surgeons' usability assessment was very favorable, with a median of 5 on a 1-5 scale. The median visual analog scale (VAS) score was 1 (range: 1-3). Conclusions: This is the first documentation of a surgery performed via the vagina using robotic instrumentation developed for this purpose. The disruptive technology of RvNOTES, with its fast learning curve, will make gynecological surgeries accessible to more women.